Normalizing CO2 in chronic hyperventilation by means of a novel breathing mask: a pilot study. (20th March 2013) - Johansen, Troels; Jack, Sandy; Dahl, Ronald
Abstract: Introduction: Chronic idiopathic hyperventilation (CIH) is a form of dysfunctional breathing that has proven hard to treat effectively. Objectives: To perform a preliminary test of the hypothesis that by periodically inducing normocapnia over several weeks, it would be possible to raise the normal resting level of CO2 and achieve a reduction of symptoms. Methods: Six CIH patients were treated 2 h a day for 4 weeks with a novel breathing mask. The mask was used to induce normocapnia in these chronically hypocapnic patients. Capillary blood gases and acid/base parameters [capillary CO2 tension (PcapCO2 ), pH, and standard base excess (SBE)] were measured at baseline and once each week at least 3 h after mask use, as well as spirometric values, breath‐holding tolerance and hyperventilation symptoms as per the Nijmegen Questionnaire (NQ). Results: The mask treatment resulted in a significant increase of resting PcapCO2 (+0.45 kPa, P  = 0.028), a moderate increase in SBE (+1.4 mEq/L, P  = 0.035) and a small reduction in daily symptoms (−3.8 NQ units, P  = 0.046). The effect was most pronounced in the first 2 weeks of treatment. Conclusion: By inducing normocapnia with the breathing mask 2 h a day for 4 weeks, the normal resting CO2 and acid/base levels in chronically hyperventilating patients were partially corrected, and symptoms were reduced.